Aplicaç\~ao de funç\~oes de distância para o cálculo de índices de bem-estar e a evoluç\~ao do índice de desenvolvimento humano (IDH) para os estados brasileiros - Marcus Vinicius Magalh\~aes de Lima; Rogério Boueri (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– Although it has an acceptance on the multidimensional nature of well-being, an unequivocal definition of the term does not exist. By the one hand utilitarian perspective prioritizes of the accumulation process and restricts the relation between well-being and the qualitative aspects of the population (normally restricted to income). By the other hand, in the perspective of opportunities, the notion of substantive freedoms of the individuals is prioritized and well-being is based on the possibilities of individual choice. In spite of the plurality of interpretations that can emerge from the different concepts, the IDH is presented as measured synthesis. Nonetheless, the use of the IDH as measured of reference presents three important methodological restrictions: the necessity of normalization of the indexes for the comparison of information with distinct nature; the arbitrary nature of the choice of the system of aggregation of individual indexes; and the difficulty of intertemporal evaluation of the observations. This study applied distance functions through data envelopment analysis (DEA), since this methodology allows to face the cited restrictions. The results obtained point to a concentration of well-being between the regions South, Southeastern and Center-West and faster indices of evolution for the states of the regions North and Northeast.
Keywords: R13; 330